Intralingvistinė interferencija lietuvių kalboje nykstančios dvikalbystės sąlygomis - Pažūsis, Lionginas (Kalbotyra, 1985)
The present paper deals with a variety of Lithuanian spoken by the second (i. e. American-born) generation of immigrants in the USA and attempts to establish a relation between intralingual interference and the conditions of subtractive bilingualism under which this variety exists. The author confines himself to the study of intralingual interference within morphology and reveals striking tendencies parallel to the established processes of intralingual interference in some other local varieties of Lithuanian existing under the similar conditions of subtractive bilingualism on the outskirts of the Lithuanian-speaking region in the home country.